2019
DOI: 10.1590/1980-549720190029
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à obesidade em rodoviários da Região Metropolitana de Belo Horizonte, Minas Gerais, Brasil

Abstract: RESUMO: Objetivo: Analisar os fatores demográficos, comportamentais e ocupacionais associados à obesidade em trabalhadores do transporte coletivo urbano de cidades da Região Metropolitana de Belo Horizonte (RMBH), Minas Gerais, Brasil. Método: Estudo transversal com 1.448 motoristas e cobradores da RMBH. Dados antropométricos, demográficos, comportamentais, de vínculo com a empresa e condições do ônibus foram coletados, em 2012, por meio de questionário aplicado face a face por entrevistador. Para o cálcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 36 publications
(72 reference statements)
4
7
0
14
Order By: Relevance
“…Moreover, over half of the participants did not comply with the recommended minimum of 150 minutes of physical activity per week for health promotion (7) . Other studies have reported high percentages of workers who did not practice physical activity, with mean values ranging from 25 to 66% (5)(6)(7)13,24) , which corroborates our findings (bus drivers -59.09%; fare collectors -53.33%). Regardless of the job, the participants exhibited levels of physical inactivity higher than the value observed for the male Brazilian population (35 to 40% are physically inactive) (25) .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Moreover, over half of the participants did not comply with the recommended minimum of 150 minutes of physical activity per week for health promotion (7) . Other studies have reported high percentages of workers who did not practice physical activity, with mean values ranging from 25 to 66% (5)(6)(7)13,24) , which corroborates our findings (bus drivers -59.09%; fare collectors -53.33%). Regardless of the job, the participants exhibited levels of physical inactivity higher than the value observed for the male Brazilian population (35 to 40% are physically inactive) (25) .…”
Section: Discussionsupporting
confidence: 92%
“…Men represented almost the entirety of the workers on the jobs analyzed in this study. This finding is similar to previous studies focused on these professions (5,8,11,12) and it seems to be related to the danger that surrounds the job considering the number of robberies and road traffic accidents (6) . In addition, the mean age of bus drivers was higher than that of fare collectors, probably due the hierarchy of jobs in the workplace and to the fact that in order to get a bus driving license (license D) in Brazil, the applicant must be 21 years of age or older and have a minimum of two years of license B (vehicles that do not exceed 8 seats) or one year of license C (cargo vehicles) (7,11) .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations